Reproductive plasticity and oogenesis in the queen honey bee (Apis mellifera). (January 2022) - Aamidor, Sarah E.; Cardoso-Júnior, Carlos A.M.; Harianto, Januar; Nowell, Cameron J.; Cole, Louise; Oldroyd, Benjamin P.; Ronai, Isobel
Graphical abstract*: Highlights: Honey bee queens are known to stop laying eggs during winter, swarming and shipment. Queens use unique oogenesis checkpoints to maintain high fecundity long term. Queens use a different combination of oogenesis 'checkpoints' compared to workers. Queens and workers use the same programmed cell death genes to regulate oogenesis. Abstract: In the honey bee ( Apis mellifera ), queen and worker castes originate from identical genetic templates but develop into different phenotypes. Queens lay up to 2000 eggs daily whereas workers are sterile in the queen's presence. Periodically queens stop laying: during swarming, when resources are scarce in winter, and when they are confined to a cage by beekeepers. We used confocal microscopy and gene expression assays to investigate the control of oogenesis in the ovaries of honey bee queens that were caged inside and outside the colony. We find evidence that queens use a different combination of 'checkpoints' to regulate oogenesis compared to honey bee workers and other insect species. However, both queen and worker castes likely use the same programmed cell death pathways to terminate oocyte development at their caste-specific checkpoints. Our results also suggest that a key factor driving the termination of oogenesis in queens is nutritional stress. Thus, queens may regulate oogenesis via the same regulatory pathways that were utilised by ancestral solitary species but likely have adjusted physiological checkpoints to suit their highly-derived life history.